2023
DOI: 10.3389/fcell.2023.1283820
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondria: one of the vital hubs for molecular hydrogen’s biological functions

Xiaoyue Zhang,
Fei Xie,
Shiwen Ma
et al.

Abstract: As a novel antioxidant, a growing body of studies has documented the diverse biological effects of molecular hydrogen (H2) in a wide range of organisms, spanning animals, plants, and microorganisms. Although several possible mechanisms have been proposed, they cannot fully explain the extensive biological effects of H2. Mitochondria, known for ATP production, also play crucial roles in diverse cellular functions, including Ca2+ signaling, regulation of reactive oxygen species (ROS) generation, apoptosis, proli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
3
1

Year Published

2024
2024
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 113 publications
0
3
1
Order By: Relevance
“…Similarly, there were no differences between the groups in terms of the quantitative measurement of the liver ATP levels (data not shown). In many cases, the treatment of stressinduced groups with hydrogen enhances ATP production 26) ; however, this phenomenon was not observed in the present study. This indicates that the induction of oxidative stress in this study (via the ingestion of ethanol 0.6 mg/kg/d for two weeks) did not cause effects strong enough to impair mitochondrial ATP production, the oxidative phosphorylation process.…”
Section: Discussioncontrasting
confidence: 87%
“…Similarly, there were no differences between the groups in terms of the quantitative measurement of the liver ATP levels (data not shown). In many cases, the treatment of stressinduced groups with hydrogen enhances ATP production 26) ; however, this phenomenon was not observed in the present study. This indicates that the induction of oxidative stress in this study (via the ingestion of ethanol 0.6 mg/kg/d for two weeks) did not cause effects strong enough to impair mitochondrial ATP production, the oxidative phosphorylation process.…”
Section: Discussioncontrasting
confidence: 87%
“…Mitochondria play a pivotal role in energy provision during maturation and subsequent development, as well as in various cellular functions, including Ca 2+ signalling, ROS production regulation, apoptosis, proliferation and lipid transport (Zhang et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…Mitochondria play a crucial role in cellular homeostasis and function as the powerhouse of the cell, involved in metabolism and signal transduction [16,17]. Studies have shown that mitochondria and the endoplasmic reticulum (ER) interact through mitochondria-associated ER membranes (MAMs) to maintain cellular balance [18,19].…”
Section: Introductionmentioning
confidence: 99%